2017
DOI: 10.3390/molecules22111975
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Cyclodextrin/TPP Nanoparticles Loaded with Quercetin as Novel Bacterial Quorum Sensing Inhibitors

Abstract: The widespread emergence of antibiotic-resistant bacteria has highlighted the urgent need of alternative therapeutic approaches for human and animal health. Targeting virulence factors that are controlled by bacterial quorum sensing (QS), seems a promising approach. The aims of this study were to generate novel nanoparticles (NPs) composed of chitosan (CS), sulfo-butyl-ether-β-cyclodextrin (Captisol®) and/or pentasodium tripolyphosphate using ionotropic gelation technique, and to evaluate their potential capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 89 publications
6
37
0
Order By: Relevance
“…Finally, it should be noted that there is an increasing number of publications in which chitosan and cyclodextrin are used as important components in the preparation of nano-vehicles or stimuli-sensitive carriers [ 170 , 185 , 191 , 200 , 201 , 202 , 203 ].…”
Section: Chitosan- Grafted -Cyclodextrin Derivamentioning
confidence: 99%
“…Finally, it should be noted that there is an increasing number of publications in which chitosan and cyclodextrin are used as important components in the preparation of nano-vehicles or stimuli-sensitive carriers [ 170 , 185 , 191 , 200 , 201 , 202 , 203 ].…”
Section: Chitosan- Grafted -Cyclodextrin Derivamentioning
confidence: 99%
“…It was reported that in metastatic ovarian cancer cells, quercetin increases the level of proapoptotic molecules such as cytochrome c, Bid, Bad, Bax, caspase-3, and caspase-9, indicating the mitochondrialmediated apoptotic pathway [31]. Similar results have been described in prostate cancer; quercetin activates caspase-3 and caspase-9 triggering apoptotic mechanisms via the mitochondrial pathway [32].The NPs used as carriers for the delivery of quercetin into target cells have been evaluated in different diseases [33,34]. On the one hand, NPs alone offers a system that causes damage to specific cells by mechanisms such as oxidative stress, lipids and proteins oxidation, and high toxicity due to their physicochemical characteristic as the superficial charge [35].…”
Section: Introductionmentioning
confidence: 60%
“…85 Suitable therapeutic compounds are not only required to display a low toxicity index, but also to have appropriate pharmacokinetic features for clinical usages. 86 Nanoparticles are also recognized as synthetic QSIs. However, more studies are required to explore these nanoparticles additionally.…”
Section: Synthetic Compoundsmentioning
confidence: 99%